SYNTHESIS OF POLY-5,7-DIALLYL-25,26,27,28-TETRAHYDROXYCALIX[4]ARENE - Desi Suci Handayani; Jumina Jumina; Maulidan Firdaus; Triana Kusumaningsih (Indonesian Journal of Chemistry, 2010)
The synthesis of poly-5,7-diallyl-25,26,27,28-tetrahydroxycalix[4]arene were performed in experimental series as follows: (1) Cyclotetramerization of p-t-butylphenol with NaOH and paraformaldehyde to p-butylcalix[4]arene, (2) Debutylation of p-butylcalix[4]arene using AlCl3 and phenol to tetrahydroxycalix[4]arene, (3) Allylation reaction using allylbromide to diallyloxy-dihydroxycalix[4]arene, (4) Claisen rearrangement reaction, (5) Cationic polymerization to diallylcalix[4]arenes. All of the synthesized products were analyzed by means of IR spectrometer and 1H-NMR spectrometer. The result of 25,27-diallyloxy-26,28-dihydroxycalix[4]arene synthesis was white crystals having m.p. 205-207 °C in 80.95% yield. The synthesis of 5,7-diallyl-25,26,27,28-tetrahydroxy-calix[4]arene gave light yellow crystals having m.p. 214-216 °C in 78.67% yield. The polymerization gave poly(5,7-diallyl-25,26,27,28-tetra-hydroxycalix[4]arene) having m.p. 338-340 °C, in 60% yield. Its estimated has a relative molecular weight of 18,738 g/mol with the number of unit repetition about 37 monomer units.